2022
DOI: 10.1097/iae.0000000000003475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Scleral Buckling and Vitrectomy in the Onset of Cystoid Macular Edema and Epiretinal Membrane After Rhegmatogenous Retinal Detachment Repair

Abstract: To investigate the incidence and risk factors for the main complications in patients with rhegmatogenous retinal detachment treated with scleral buckling (SB) or pars plana vitrectomy (PPV).Methods: A retrospective, comparative, observational study was conducted. The medical records of 107 patients with primary rhegmatogenous retinal detachment who were managed with SB (n = 57) or PPV (n = 50) were reviewed. Scleral buckling was performed using scleral encircling solid silicone band and circumferential solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The current study finds that postoperative ERM after PPV or combined PPV/SB for GRT-RD repair is 70.6%, a significantly higher incidence when compared to a routine RRD repair with a reported incidence of 12.1% to 30.8%. 14,15,17,18,20 One study has shown that the incidence of ERM after PPV for a routine RRD could be as high as 70.3% using en face OCT, 21 likely due to its high sensitivity, whereas the current and most of the other studies 14,15,17,18,20 have analyzed spectral-domain OCT for presence of ERM. Studies have suggested that epiretinal proliferation has multiple etiologies including RPE cell migration through a full-thickness retinal break, retinal glial cells as well as vitreous components including platelet-derived growth factors, cytokines and blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…The current study finds that postoperative ERM after PPV or combined PPV/SB for GRT-RD repair is 70.6%, a significantly higher incidence when compared to a routine RRD repair with a reported incidence of 12.1% to 30.8%. 14,15,17,18,20 One study has shown that the incidence of ERM after PPV for a routine RRD could be as high as 70.3% using en face OCT, 21 likely due to its high sensitivity, whereas the current and most of the other studies 14,15,17,18,20 have analyzed spectral-domain OCT for presence of ERM. Studies have suggested that epiretinal proliferation has multiple etiologies including RPE cell migration through a full-thickness retinal break, retinal glial cells as well as vitreous components including platelet-derived growth factors, cytokines and blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, considering all 12 eyes of our study, no post-operative macular OCT has shown the onset of cystoid macular edema (CME), which represents a common complication in standard PPV. In fact, recent studies have highlighted that the incidence of CME after rhegmatogenous retinal detachment repair was higher in patients who underwent PPV, either alone or combined with phacoemulsification than in those treated with SB [ 29 ]. Probably, the use of cryotherapy retinopexy instead of endolaser retinopexy [ 30 ] plays a role in lowering the risk of post-operative CME.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a substantial proportion (15.8%) of our patients had undergone SB. Gharbiya et al [19] showed that PSME was more common after vitrectomy (26.0%), either alone or combined with CS, than after SB (5.3%). Lai et al [21] found that the risk factors associated with PSME after SB were older age, more extended RRD, macular detachment, and external drainage.…”
Section: Discussionmentioning
confidence: 99%